Modified Sensory Testing in Non-verbal Patients Receiving Novel Intrathecal Therapies for Neurological Disorders - Cornelissen, Laura; Donado, Carolina; Yu, Timothy W.; Berde, Charles B. (Frontiers in Neurology, 2022)
Several neurological disorders may be amenable to treatment with gene-targeting therapies such as antisense oligonucleotides (ASOs) or viral vector-based gene therapy. The US FDA has approved several of these treatments; many others are in clinical trials. Preclinical toxicity studies of ASO candidates have identified dose-dependent neurotoxicity patterns. These include degeneration of dorsal root ganglia, the cell bodies of peripheral sensory neurons. Quantitative sensory testing (QST) refers to a series of standardized mechanical and/or thermal measures that complement clinical neurologic examination in detecting sensory dysfunction. QST primarily relies on patient self-report or task performance (i.e., button-pushing). This brief report illustrates individualized pragmatic approaches to QST in non-verbal subjects receiving early phase investigational intrathecal drug therapies as a component of clinical trial safety protocols. Three children with neurodevelopmental disorders that include Neuronal Ceroid Lipofuscinosis Type 7, Ataxia-Telangiectasia, and Epilepsy of Infancy with Migrating Focal Seizures are presented. These case studies discuss individualized testing protocols, accounting for disease presentation, cognitive and motor function. We outline specific considerations for developing assessments for detecting changes in sensory processing in diverse patient groups and safety monitoring trials of early phase investigational intrathecal drug therapies. QST may complement information obtained from the standard neurologic examination, electrophysiologic studies, skin biopsies, and imaging. QST has limitations and challenges, especially in non-verbal subjects, as shown in the three cases discussed in this report. Future directions call for collaborative efforts to generate sensory datasets and share data registries in the pediatric neurology field.